2008
DOI: 10.1007/s11064-008-9824-4
|View full text |Cite
|
Sign up to set email alerts
|

Nestin in the Temporal Neocortex of the Intractable Epilepsy Patients

Abstract: Nestin is one kind of intermediate filament protein, which is considered as a typical marker of neural precursor cells. Considerable evidence supports nestin may have actively functions in neurogenesis and gliosis. Our aim was to investigate nestin expression in the temporal neocortex of patients with intractable epilepsy (IE), and then to discuss the possible role of nestin in IE. Tissue samples from the temporal neocortex of 32 patients who had surgery for IE were used to detect nestin expression by immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Most nestin‐positive cells in epileptic patients show an astrocyte‐like form with characteristic sharp multipolar processes 12,13 . It is considered that nestin‐positive cells may be derived from astrocytes or neural precursor cells and play a role in the reconstruction of glia 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Most nestin‐positive cells in epileptic patients show an astrocyte‐like form with characteristic sharp multipolar processes 12,13 . It is considered that nestin‐positive cells may be derived from astrocytes or neural precursor cells and play a role in the reconstruction of glia 14,15 …”
Section: Introductionmentioning
confidence: 99%
“…Neuron loss was a predominant pathological change in the epileptogenic zones; the present study demonstrated this pathological change. After seizures, neuronal survival and neurogenesis were also observed in the brain tissue of patients [2]. Up-regulation of IR after seizures might participate in the regulation of neuronal loss and neuronal survival, which are both consequences that can be induced by seizures.…”
Section: Discussionmentioning
confidence: 97%
“…Immunostaining was performed on the paraffin sections as reported previously [2]. Counterstaining was done using Harris hematoxylin.…”
Section: Immunohistochemistry and Double-label Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…There has been found some abnormal expression of proteins such as nestin, aquaporin-1, slit-2, and TGF-β1 that appear under pathological injuries such as seizure. Therefore, altered astrocytes disturb the interneural and astrocyte-neuron interaction, promoting the development of RE [1618]. …”
Section: The Pathomechanism Of Refractory Epilepsymentioning
confidence: 99%